Queer Cinema in the World by Karl Schoonover and Rosalind Galt (review) - Llamas-Rodriguez, Juan (QED: A Journal in GLBTQ Worldmaking, 2018)
Karl Schoonover and Rosalind Galt attempt a formidable feat in Queer Cinema in the World: to take three charged yet indispensable concepts and theorize their interconnections. A tour-de-force analysis of the triangulation between “queer,” “cinema,” and “world”, this coauthored monograph largely succeeds in drawing out threads between crucial issues in cinema studies, queer theory, and global studies.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé